2016
DOI: 10.1007/s00540-016-2248-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of pectoral nerve block for the management of zoster-associated pain: case reports and technical description

Abstract: The recently introduced pectoral nerve (Pecs) block is a simple alterative to the conventional thoracic paravertebral block or epidural block for breast surgery. It produces excellent analgesia and can be used to provide balanced anesthesia and as a rescue block in cases where performing a neuraxial blockade is not possible. In the thoracic region, a neuraxial blockade is often used to manage zoster-associated pain. However, this can be challenging for physicians due to the increased risk of hemodynamic instab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Ultrasound guided peripheral nerve blocks may become a valid alternative to neuraxial blocks in case of contraindications or ineffectiveness of the latter, as was the case of our patient [79].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Ultrasound guided peripheral nerve blocks may become a valid alternative to neuraxial blocks in case of contraindications or ineffectiveness of the latter, as was the case of our patient [79].…”
Section: Discussionmentioning
confidence: 68%
“…There are few reports of peripheral nerve blocks used to treat PHN. The use of a PECS II block and of an erector spinae (ESP) block has been reported in cases of HZ-related acute pain or PHN, where neuraxial block was ineffective or impossible to perform [710]. A randomized controlled trial demonstrated that repetitive paravertebral anaesthetic block in combination with oral standard treatment significantly reduced the incidence of PHN compared to standard treatment alone [13]; however, only one case report described the successful application of a continuous paravertebral block using a paravertebral catheter to treat a case of PHN [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A peripheral nerve block may be used as an alternative option with which to treat localized peripheral neuralgia, as irritable peripheral nociceptors are responsible for the spontaneous pain and allodynia [1]. We read with interest the article by Kim YD et al suggested the clinical usefulness of US-guided Pecs II blocks with which to treat PHN in patients for whom a neuroaxial block was contraindicated due to taking anticoagulants [2]. In addition, we report a patient with a localized intractable thoracic PHN who did not respond to various treatments, but in whom the US-guided Pecs II block induced symptoms improvement.…”
Section: To the Editormentioning
confidence: 99%